Сучасні підходи до лікування виразкової хвороби шлунка та перспективи використання засобів біологічної терапії - Кошурба, І.В.; Гладких, Ф.В.; Чиж, М.О. (Modern approaches to the treatment of peptic ulcer disease and prospects for the use of biological therapy. Modern Medical Technology (2), 58-66., 2023)
Digestive diseases are the sixth leading cause of death in the world and accounted for more than 2.5 million deaths in 2019. In Ukraine, mortality from diseases of the digestive system is recorded as one of the highest in the world, and the leading place in the general structure of diseases of the digestive system is occupied by peptic ulcer disease (РUD). The aim of the study. Summarize current information on the etiology and the pathogenesis of РUD and characterize modern approaches to the treatment of patients with РUD and the prospects of biological therapy. Materials and methods. Publications were selected based on the PubMed, Clinical Key Elsevier, Cochrane Library, eBook Business Collection, and Google Scholar databases, which covered information on the etiology, pathogenesis, and approaches to the treatment of РUD. Results. Standard first-line anti-Helicobacter therapy consists of a proton pump inhibitor and two antibiotics, such as clarithromycin and amoxicillin or metronidazole. A promising direction in the treatment of РUD is the use of biological therapy. According to literature sources, the prophylactic use of cryoextract of the placenta in indomethacin gastric lesions has an anti-ulcer effect at the level of 69.1 % and 92.1 % in diclofenac sodium gastric lesions. In addition, the specified cryoextract is capable of leveling the gastrotoxic effect of acetylsalicylic acid, ibuprofen, stress factor and chemical ulcerogens. Conclusions. Today, there is a great need for cell therapy that could be put into practice in clinically relevant volumes. The most promising directions of biological therapy in gastroenterology are considered to be the use of mesenchymal stem cells and agents obtained from the fetoplacental complex.
Modern approaches to the treatment of peptic ulcer disease and prospects for the use of biological therapy
Koshurba, I. V., Hladkykh, F. V., & Chyzh, M. O. (2023). Modern approaches to the treatment of peptic ulcer disease and prospects for the use of biological therapy. Modern Medical Technology, (2), 58-66. https://doi.org/10.34287/MMT.2(57).2023.10
Keywords: peptic ulcer; Helicobacter pylori; clarithromycin; placenta cryoextract